Globalizing capital a history of the international monetary system - Eichengreen, Barry J. (Princeton University Press, 2019)
"Essential reading for understanding the international economy--now thoroughly updated Lucid, accessible, and provocative, and now thoroughly updated to cover recent events that have shaken the global economy, Globalizing Capital is an indispensable account of the past 150 years of international monetary and financial history--from the classical gold standard to today's post-Bretton Woods 'nonsystem.' Bringing the story up to the present, this third edition covers the global financial crisis, the Greek bailout, the Euro crisis, the rise of China as a global monetary power, the renewed controversy over the international role of the U.S. dollar, and the currency war. Concise and nontechnical, and with a proven appeal to general readers, students, and specialists alike, Globalizing Capital is a must-read for anyone who wants to understand where the international economy has been--and where it may be going"--